Comparison of results of aortic valve replacement through median sternotomy and mini sternotomy in overweight patients - Aliahmed, Hammad Mohammad Ahmad; Podkopajev, Andrej; Samėnienė, Palmyra (Lietuvos chirurgija, 2017)
BackgroundThe article provides a comparative analysis of results of aortic valve replacement through median sternotomy and mini sternotomy in overweight patients.MethodsThis is a retrospective study of patients, who had overweigh (BMI > 25 kg/m2) and underwent an isolated replacement of the aortic valve by sternotomy or mini sternotomy in the period from 2011 to 2016. Through propensity score matching, 56 patients (mini sternotomy group) were compared with 56 patients in full sternotomy (control group).ResultsMini sternotomy had longer cross clamp 91 ± 20 min vs 76 ± 23 min (p < 0.001), longer operative time 264 ± 62 min vs 246 ± 72 min (p = 0.046) and bypass times 148 ± 4 min vs 133 ± 2 min (р = 0,023). In the mini sternotomy group acute renal failure developed less frequently – 2 pts. (3.6%) vs 12 pts. (21.43%) (p = 0.004).We did not find significant differences in the hospital stay, intensive care unit stay, ventilation time and postoperative blood loss.ConclusionsMinisternotomy is a safe method for surgical aortic valve replacement for overweight patients. Since the results are similar, and sometimes better than after full sternotomy, we believe that this minimally invasive access can be recommended as a safe and less traumatic alternative to aortic valve replacement in overweight patients.
Keywords: ministernotomy; sternotomy; aortic valve stenosis; patients with overweight